Web-Based Lecturer Performance Selection Information System Using Weighted Product (WP) Method - Deni Arsandi; Novita br Ginting; Dewi Primasari (Jurnal Mantik, 2021)
Academic Informatics Management (AMIK) Bogor is a college in Bogor, where the performance appraisal process uses a questionnaire distributed to students for lecturer performance appraisal, the assessment set at the Informatics Management Academic is done by simple calculations looking for the highest score. it is still quite difficult and not accountable in concluding the performance results of a lecturer because the assessment is only done by students. So from these problems the calculation using the weight product method is able to calculate the performance of lecturers with precise accuracy